Integrative transcript to proteome analysis of barley during Ramularia collo-cygni leaf spot development identified several proteins that are related to fungal recognition and infection responses - Lemcke, René; Kamble, Manoj; Schneider, Sebastian; Lyngkjær, Michael F.; Radutoiu, Simona; Wienkoop, Stefanie (Frontiers in Plant Science, 2024)
Introduction Ramularia leaf spot (RLS) disease is a growing threat to barley cultivation, but with no substantial resistance identified to date. Similarly, the understanding of the lifestyle of Ramularia collo-cygni (Rcc) and the prediction of RLS outbreak severity remain challenging, with Rcc displaying a rather untypical long endophytic phase and a sudden change to a necrotrophic lifestyle. The aim of this study was to provide further insights into the defense dynamics during the different stages of colonization and infection in barley in order to identify potential targets for resistance breeding. Methods Utilizing the strength of proteomics in understanding plant–pathogen interactions, we performed an integrative analysis of a published transcriptome dataset with a parallel generated proteome dataset. Therefore, we included two spring barley cultivars with contrasting susceptibilities to Rcc and two fungal isolates causing different levels of RLS symptoms. Results Interestingly, early responses in the pathogen recognition phase of the host were driven by strong responses differing between isolates. An important enzyme in this process is a xylanase inhibitor, which protected the plant from cell wall degradation by the fungal xylanase. At later time points, the differences were driven by cultivar-specific responses, affecting mostly features contributing to the pathogenesis- and senescence-related pathways or photosynthesis. Discussion This supports the hypothesis of a hemibiotrophic lifestyle of Rcc, with slight differences in trophism of the two analyzed isolates. The integration of these data modalities highlights a strength of protein-level analysis in understanding plant–pathogen interactions and reveals new features involved in fungal recognition and susceptibility in barley cultivars.